SYMBIOTIC ASSOCIATIONS IN MARINE SPONGES - Harpeni, Esti (Jurusan Perikanan dan Kelautan, 2025)
The characteristics of the sponge structure, homogenous, flexible, and simple, but pervaded by canals and their ability for filter-feeding, may facilitate development of intimate associations with other organisms. This study reviewed the described symbiotic associations between marine sponges and other organisms as well as among marine sponge species. Associations in marine sponges show a wide range of relationships with their symbionts. These can range from mutually beneficial, to commensal, to parasitic or pathogenic. Sponge species also vary in the types of symbionts they host from facultative sponge associates that also live in other sheltered habitats, to obligate sponge associates that occupy a variety of sponge species, to obligate specialists on particular sponge species. The associations can cause the morphological alteration of the symbionts and other adaptive behaviour. Observations of new and unique associations were also discussed.